Moderation Of Corporate Governancein Influence Tax Avoidanceon Company Value - Indira Mayani; Lukman Effendy (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study examines the impact of tax avoidance on the value of companies with corporate governance projected by audit quality as a moderation variable. The research was conducted at a manufacturing company in Indonesia listed on the Indonesian Stock Exchange (BEI) for the period 2020-2022. This study uses a quantitative approach and population in this study of 233 companies. The samples were selected using purposive sampling, so a total of 86 companies met the criteria. The data testing method used is panel data regression analysis with the Eviews 12 software program. The results of the study showed that tax avoidance had a negative and insignificant impact on the company's value, with a coefficient value of -0.007989 and a probability value of 0.9043, which is greater than > 0.05. Corporate governance projected by the audit quality had a positive but insignificant effect on the value of the company, with the coefficient value of 0.472946 and the probability rate of 0.3260, which is larger than >0.05.